A transatlantic zero agreement: Estimating the gains from transatlantic free trade in goods - Fredrik Erixon; Matthias Bauer (European Centre for International Political Economy (ECIPE), 2010)
This study examines the potential gains from a transatlantic zero-tariff agreement on trade in goods. The idea of deeper transatlantic economic integration has become more attractive in recent years. The hopes for an ambitious multilateral trade deal in the Doha Round negotiations have diminished; few countries appear ready to accept ambitious liberalisation on the global level. Leaders have increasingly turned to bilateral or regional trade initiatives, but few of them are capable of delivering sizeable gains to big economies like the European Union and the United States. (...)
Keywords: 330; Handelsabkommen; Wirkungsanalyse; USA; EU-Staaten